Архітектурно-планувальна трансформація рекреаційних систем приміських зон великих міст (на прикладі міста Львова) - Покладок, Ольга Володимирівна (Національний університет "Львівська політехніка", 2021)
Дисертація присвячена вивченню питання архітектурно-планувальної трансформації рекреаційної системи в приміській зоні Львова, виявленню особливостей та тенденцій цієї трансформації, розробленню науково-методичних основ архітектурно-планувальної організації та розвитку рекреаційної системи (РС) на цій території. З’ясовано місце і значення РС в приміській зоні - вона виступає рівнозначною з іншими системами. Аналіз трансформацій РС приміської зони здійснено на макрорівні, мезорівні та мікрорівні. На основі досліджень території, об’єктів та їх аналізу створено модель просторової організації приміської рекреаційної системи Львова. Визначено перспективні рекреаційні території, які формуються на об’єднанні та створенні зв’язків між розосередженими локальними рекреаційними територіями шляхом їх сполучення між собою та існуючою системою розселення. Запропоновано ряд практичних рекомендацій та схему формування приміської рекреаційної системи. Пропозиції зосереджені на рівнях: реформування і розвитку рекреаційної схеми всієї приміської території, вибраного рекреаційного вузла, а також окремого рекреаційного об’єкта. Концепція функціонально-планувального розвитку рекреації у приміській системі м. Львова дозволила виділити перспективні рекреаційні райони. The dissertation is devoted to the study of architectural and planning transformation of the recreational system in the suburban area of Lviv, identifying features and trends of this transformation, development of scientific and methodological foundations of architectural and planning organization and development of recreational system (RS) in this area. The world experience of the organization of suburban recreational systems is studied. The unity of recreational spaces is most organized in the suburban areas of large cities in Poland and Germany. For recreational centers of Ukraine - each local recreational facility operates on its own without coordinated interaction with other territorial elements, disorder of the existing structure, which causes congestion of the territory, and leads to uncontrolled development of suburban recreational system, deteriorating environmental comfort in natural complexes.The place and significance of RS in the suburban area have been clarified - it is equivalent to other systems. The analysis of RS transformations in the suburban zone was carried out at the macro level, meso level and micro level. The basic requirements to architectural and planning re-development of recreational-developed territories and objects are defined: increase of attractiveness of recreational territories; differentiation of recreation areas by comfort; the use of new energy-efficient materials and structures, as well as new construction technologies in the construction of individual facilities and landscaping of recreational facilities. Changes in the recreational system and architecture of the objects are analyzed. Based on the research of the territory, objects and their analysis, a model of spatial organization of the suburban recreational system of Lviv was created. Promising recreational areas are identified, which are formed by combining and creating links between scattered local recreational areas by connecting them with each other and the existing settlement system. A number of practical recommendations and a scheme for the formation of a suburban recreational system are proposed. The proposals focus on the levels of: reforming and developing the recreational scheme of the entire suburban area, the selected recreational area, as well as a single recreational facility. The concept of functional and planning development of recreation in the suburban system of Lviv allowed to identify promising recreational areas. Диссертация посвящена изучению вопроса архитектурно-планировочной трансформации рекреационной системы в пригородной зоне Львова, выявлению особенностей и тенденций этой трансформации, разработке научно-методических основ архитектурно-планировочной организации и развития рекреационной системы (РС) на этой территории. Выяснено место и значение РС в пригородной зоне - она выступает равнозначной с другими системами. Анализ трансформаций РС пригородной зоны осуществлено на макроуровне, мезоуровне и микроуровне. На основе исследований территории, объектов и их анализа создана модель пространственной организации пригородной рекреационной системы Львова. Определены перспективные рекреационные территории, которые формируются на объединении и создании связей между рассредоточенными локальными рекреационными территориями путем их соединения между собой и существующей системой расселения. Предложен ряд практических рекомендаций и схема формирования пригородной рекреационной системы. Предложения сосредоточены на уровнях: реформирования и развития рекреационной схемы всей пригородной территории, выбранного рекреационного узла, а также отдельного рекреационного объекта. Концепция функционально-планировочного развития рекреации в пригородной системе м. Львова позволила выделить перспективные рекреационные районы.
Architectural and planning transformation of the recreational systems of suburban areas of large cities (for example, the city of Lviv)
Архитектурно-планировочная трансформация рекреационных систем пригородных зон крупных городов (на примере города Львова)
Keywords: архітектурно-планувальна організація; рекреаційний об’єкт; рекреаційна територія; приміська рекреаційна зона; архітектурнопланувальна трансформація; architectural and planning organization; recreational facility; recreational area; suburban recreation area; архитектурно-планировочная организация; рекреационный объект; рекреационная территория; пригородная рекреационная зона; архитектурно-планировочная трансформация; 711.4; 711.558; 711.557; 712.25; 712.01